2018
DOI: 10.1111/ffe.12807
|View full text |Cite
|
Sign up to set email alerts
|

On the notch sensitivity of flax fibre metal laminates under static and fatigue loading

Abstract: Damage progression and failure characteristics of open‐hole flax fibre aluminium laminate (flax‐FML) specimens subjected to quasi‐static tensile or tension‐tension fatigue loading were experimentally investigated. Notched and unnotched flax‐FML composites exhibited brittle fracture with little or no fibre pull‐out and minimal delamination at the aluminium/adhesive interface. The flax‐FMLs were tested to failure under tension‐tension fatigue loading conditions (R ratio of 0.1; frequency of 10 Hz; applied fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Feng et al 175 obtained similar results when the absolute and specific mechanical properties of pineapple leaf fiber‐reinforced FMLs were compared with those of composites and fabric counterparts; that is, the absolute and specific mechanical properties of the FMLs were higher than those of composites and fabric counterparts. Kandare et al 176 examined the effect of notch sensitivity on the static and dynamic properties of flax‐based FMLs. Their tensile strengths were found to decrease as the diameter‐to‐width ratio of the notch increased.…”
Section: Natural Fiber‐based Fmlsmentioning
confidence: 99%
“…Feng et al 175 obtained similar results when the absolute and specific mechanical properties of pineapple leaf fiber‐reinforced FMLs were compared with those of composites and fabric counterparts; that is, the absolute and specific mechanical properties of the FMLs were higher than those of composites and fabric counterparts. Kandare et al 176 examined the effect of notch sensitivity on the static and dynamic properties of flax‐based FMLs. Their tensile strengths were found to decrease as the diameter‐to‐width ratio of the notch increased.…”
Section: Natural Fiber‐based Fmlsmentioning
confidence: 99%
“…However, the curve started to rise sharply at the strain value of approximately 9%. The T A B L E 1 Physical and tensile properties of annealed aluminum 5052 [22,23] Designation Density (g/cm subtle stress increase at the initial stage of the stressstrain curve of ramie fabric is predominantly due to the decrimping and crimp interchange. These results are in agreement with the findings obtained by Misnon et al [31] in which the curve of hemp fabric increased with a low slope owing to the decrimping and crimp interchange.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The absolute and specific mechanical properties of basalt‐based FMLs were found to be greater than those of hemp‐ and flax‐based FMLs. Kandare et al [ 22 ] investigated the notch sensitivity on the tensile properties of flax fiber‐based FMLs. It was found that introducing the notch on the FMLs reduced the tensile strength.…”
Section: Introductionmentioning
confidence: 99%